Status Gizi dan Antenatal Care terhadap Kejadian Stunting pada Anak Balita - Fitri Diana Astuti; Iin Inayah; Fauziah Rudhiati; Siti Yuyun Rahayu Fitri; Murtiningsih Murtiningsih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the factors affecting the incidence of stunting in children under five in the working area of the Lohia Public Health Center, Muna Regency, in 2022. This research method is a quantitative study with a case-control study design. The results showed that 25 respondents (69.4%) had non-standard antenatal care and stunting, and 11 (30.6%) had non-standard and non-stunted antenatal care. While standard antenatal care and stunting amounted to 17 respondents (35.4%), routine antenatal care and stunting amounted to 17 respondents (35.4%). The statistical test obtained a significant value (p-value) of 0.002. In conclusion, there is an important influence between the nutritional status of pregnant women and antenatal care on the incidence of stunting in toddlers at the Lohia Health Center, Muna District. Keywords: Antenatal Care, Pregnant Women, Nutritional Status, Stunting